Effects of the HEP® (Homeostasis–Enrichment–Plasticity) Approach in preterm infants with increased developmental risk: a randomized controlled study - Sirma, Gamze Cagla; Zengin Alpozgen, Ayse; Balikci, Aymen (Frontiers in Pediatrics, 2025)
Background and objectivesThis study investigated the effectiveness of the Homeostasis-Enrichment-Plasticity (HEP) Approach in preterm infants with increased developmental risk, compared to the Traditional Treatment (TT) intervention for physical and occupational therapy.Materials and methodsTwenty-nine preterm infants (adjusted age, 4–10 months) were randomly assigned to two groups: the HEP Approach group and the TT group. The Peabody Developmental Motor Scales-2 (PDMS-2), Test of Sensory Functions in Infants (TSFI), and Beck Anxiety Inventory (BAI) were administered pre- and post-intervention. The intervention was implemented weekly for 12 weeks.ResultsThe baseline characteristics of the infants were similar. At the end of the treatment, a significant time effect was observed in motor skills and sensory functions across both groups, with improvements in all PDMS-2 and TSFI subtests (p < 0.05). Significant time × group interactions showed greater improvements in the HEP Approach group compared to the TT group for Fine Motor Quotient: F = 10.818, p = 0.003; Gross Motor Quotient: F = 5.691, p = 0.024; and Total Motor Quotient: F = 21.109, p < 0.001. For TSFI, the HEP Approach group showed greater improvements in Adaptive Motor Functions (F = 13.794, p = 0.001), Visual-Tactile Integration (F = 7.410, p = 0.011), and Total score (F = 11.316, p = 0.002). No significant time*group interactions were found for Reactivity to Tactile Deep Pressure, Ocular Motor Control, and Reactivity to Vestibular Stimulation (p > 0.05). Parental anxiety, measured by BAI, decreased significantly in both groups (F = 8.72, p = 0.006), but no significant time × group interaction was found (p > 0.05), indicating similar reductions in both groups.ConclusionThe HEP Approach demonstrated superior outcomes compared to the TT intervention in improving motor skills and sensory functions in preterm infants, while both interventions reduced caregiver anxiety.